RANCANG BANGUN TRANSMISI PADA POROS MESIN PELONTAR PAKAN IKAN OTOMATIS - Hidayat, Ahmad Wahyu; Ramdani, Rizki (Jurnal Mahasiswa Terapan, 2024)
The increase in fishery production in Indonesia faces challenges in fish feeding, which is still done manually. This manual feeding system requires a long time and often does not meet the needs of the fish, affecting their growth and health. To address this issue, this research designs and develops a transmission system for an automatic fish feed launcher machine. The machine is designed using mechanical and electrical systems integrated with Arduino Uno R3 and a Real-Time Clock (RTC) to regulate the schedule and amount of feed dispensed. The designed transmission system uses pulleys and a V-belt to enhance efficiency and the range of feed dispersal. The results of this research are expected to improve fish farmers' productivity by providing automatic feeding that is timely and in the correct quantity, thereby reducing feed waste and increasing the efficiency of fish farming.